Analisis determinan tingkat suku bunga dan di Indonesia Tahun 1990-2020 (Pendekatan Error Corection Model) - Erwin , Geiskha; Tan, Syamsurijal; Hodijah, Siti (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2023)
This study aims to analyze the development of interest rates, exchange rates, economic growth and government spending in Indonesia in 1990-2020. To analyze the effect of Exchange Rates, Economic Growth, and Government Expenditures on Interest Rates in Indonesia in 1990-2020. The data used in this study is secondary data which was analyzed using the Eviews tool, with the Error Correction Model analysis method. During the period 1990-2020. Based on the results of testing interest rates in Indonesia during the period 1990-2020 using the ECM method, the results show that simultaneously in the long and short term, the variables of Exchange, PE, and Government Expenditures have a significant effect on Interest Rates. Meanwhile, based on the partial test results in the long term, economic growth has a significant effect on interest rates in Indonesia. The exchange rate variable partially in the long term and short term has a significant effect on interest rates, while the Indonesian government's spending in the long term period 1990-2020 has a significant effect, and the short term is not significant.